Do pé à letra : os amores de Ovídio em tradução poética - Duque, Guilherme Horst (2015)
Based on the writings of Haroldo de Campos, we understand that translating differs very little from the exercise of literary criticism. As an activity that presumes the keen study and close reading of the material to be translated, translating is constituted by an analysis of the text followed by its reworking, executed in such a way as to share meaningful aspects of the original’s composition. With that in mind, and taking as point of departure the works of João Angelo Oliva Neto, Raimundo Carvalho, Guilherme G. Flores and João Paulo Matedi, I present here the full translation of the Amores from P. Ovid Naso along with an introductory essay, which exposes, in a panoramic way, part of the reflections that were developed throughout the task of converting to Portuguese the elegies of the poet of Sulmo.